2019
DOI: 10.1111/jce.14213
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar radiofrequency ablation creates different lesion characteristics compared to simultaneous unipolar ablation

Abstract: Introduction Both bipolar and simultaneous radiofrequency ablation (bRFA, simRFA) have been used to treat thick midmyocardial substrate as well as during circular, multipolar ablation between shorter distances. Objectives We sought to evaluate the biophysical parameters of simRFA, sequential unipolar RFA (seqRFA), and bRFA. Methods Bovine myocardium was placed in a circulating saline bath. To simulate thick substrate conditions, two open irrigated ablation catheters were oriented across from each other, with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
0
29
1
Order By: Relevance
“…However, an experimental study reported that bipolar RFCA has higher core lesion temperatures, corresponding to a denser and larger necrotic core, than simultaneous unipolar RFCA. 25…”
Section: Discussionmentioning
confidence: 99%
“…However, an experimental study reported that bipolar RFCA has higher core lesion temperatures, corresponding to a denser and larger necrotic core, than simultaneous unipolar RFCA. 25…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, bipolar ablation has been shown to produce different lesion characteristics with increased lesion depth and volume compared to simultaneous unipolar ablation. 16 Clinically, bipolar ablation has been efficacious in treating refractory arrhythmias from the outflow tracts, LV summit, and interventricular septum. 17 For typical ablation of septal VAs, the catheters are positioned at the sites of earliest activation and opposite of the interventricular septum.…”
Section: Bipolar Ablationmentioning
confidence: 99%
“…In animal models, bipolar ablation has been shown to produce different lesion characteristics with increased lesion depth and volume compared to simultaneous unipolar ablation. 16 Clinically, bipolar ablation has been efficacious in treating refractory arrhythmias from the outflow tracts, LV summit, and interventricular septum. 17 For typical ablation of septal VAs, the catheters are positioned at the sites of earliest activation and opposite of the interventricular septum.…”
Section: Bipolar Ablationmentioning
confidence: 99%